Kinetics of sulphur dissolution in lithium–sulphur batteries. (1st April 2022) - Dent, Matthew; Jakubczyk, Ewa; Zhang, Teng; Lekakou, Constantina
Abstract: This study investigates and determines the dissolution kinetics of solid sulphur in DOL:DME solution, a typical electrolyte solution for lithium–sulphur (Li–S) batteries, at four different temperatures, in the range of 17 °C–20 °C. The dissolution kinetics is considered as a function of the solid sulphur-solution interfacial area. The analysis yielded fast dissolution kinetics with a mass transfer coefficient of 2.3 × 10 −3 m s −1 at 20 °C but low sulphur solubility of 0.058 S mol lt −1, with the latter being a limiting factor in sulphur dissolution. In later stages, swelling of the solid sulphur region was also observed as a function of time from which the diffusion coefficient of the DOL:DME solution in the solid sulphur was determined. A novel model for the sulphur dissolution and electrolyte impregnation in a Li–S cathode in battery fabrication is presented taking into account the pore size distribution of the cathode host. A computer simulation was carried out and the model and the dissolution parameter values were validated by comparing the predictions with experimental data from in operando microscopy during the dissolution of sulphur and infiltration of the DOL:DME solution in a commercial sulphur-conductive carbon cathode.